PENGARUH LITERASI KEUANGAN DAN PENGALAMAN INVESTASI TERHADAP PENGAMBILAN KEPUTUSAN INVESTASI SAHAM PADA GALERI INVESTASI DI KOTA KEDIRI - Rahmasari, Mayang Dwi; Puspita, Nindi Vaulia (Universitas Nusantara PGRI Kediri, 2023)
This study aims to determine the effect of financial literacy and investment experience on stock investment decision making at investment galleries in Kediri City. The population in this study are investors who invest in the capital market in the Kediri region at Investment Galleries, namely the Kadiri University Investment Gallery, the Kediri Islamic University Investment Gallery, the Nusantara PGRI University Investment Gallery and the PSDKU POLINEMA Investment Gallery. The data collection technique used in this study is by using a questionnaire distributed via google form, while the data analysis technique uses multiple linear regression, classical assumption tests and hypothesis testing such as t test, F test and coefficient of determination test (R2) with the help of analytical tools IBM SPSS Version 26. The results of this study indicate that there is a significant influence of the financial literacy variable on stock investment decision making, besides that the investment experience variable also has a significant influence on stock investment decision making.